2022
DOI: 10.3390/ph16010058
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge of the Antidepressant Activity of Chemical Compounds from Crocus sativus L.

Abstract: Psychotropic effect of Crocus sativus L. (family Iridaceae) biologically active chemical compounds are quite well documented and they can therefore be used in addition to the conventional pharmacological treatment of depression. This systematic review on antidepressant compounds in saffron crocus and their mechanisms of action and side effects is based on publications released between 1995–2022 and data indexed in 15 databases under the following search terms: antidepressant effect, central nervous system, Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 349 publications
0
2
0
2
Order By: Relevance
“…A total of 328 fungal isolates were found in leaf, stem and root tissues of plants by Hafeez et al, and 12 endophytic fungal species were identified by molecular characterization [ 39 ]. Crocus sativus L. (family Iridaceae) has been widely used as an antimicrobial, antidepressant, digestive, anticancer, and anticonvulsant medicine due to its abundant natural products as well as antioxidant activity [ 40 , 41 ]. Lu et al [ 42 ] isolated endophytic fungi from five different locations in Crocus sativus tissues (corm, scape, leaf, petal, and stigma) and identified a total of 32 endophytic fungal groups, assigned to seven orders within four classes.…”
Section: Medicinal Plants and Their Cultivable Endophyte Resourcesmentioning
confidence: 99%
“…A total of 328 fungal isolates were found in leaf, stem and root tissues of plants by Hafeez et al, and 12 endophytic fungal species were identified by molecular characterization [ 39 ]. Crocus sativus L. (family Iridaceae) has been widely used as an antimicrobial, antidepressant, digestive, anticancer, and anticonvulsant medicine due to its abundant natural products as well as antioxidant activity [ 40 , 41 ]. Lu et al [ 42 ] isolated endophytic fungi from five different locations in Crocus sativus tissues (corm, scape, leaf, petal, and stigma) and identified a total of 32 endophytic fungal groups, assigned to seven orders within four classes.…”
Section: Medicinal Plants and Their Cultivable Endophyte Resourcesmentioning
confidence: 99%
“…Возможно, положительная динамика психоэмоциональных и нейровегетативных симптомов связана с влиянием кроцина и сафранала на синаптическую передачу моноаминных соединений, изменением уровня таких нейротрансмиттеров, как серотонин, дофамин, норадреналин [24,25], и с повышением уровня нейротрофического фактора (BDNF), нейропептида VGF, транскрипционного фактора CREB и P-CREB [26].…”
Section: обзорыunclassified
“…Sugars (including gums, starch, reducing sugars, pectin, dextrins, and pentosans) make up about 63% of saffron's chemical composition (although this can vary depending on the environmental conditions in the country of origin), along with 12% protein, 10% water, 5% minerals, 5% crude bre, 5% fat and traces of ribo avin and thiamine vitamins [17]. It is having various therapeutic properties such as insomnia, alzheimer's disease [18], neuropsychiatric and age-related diseases [19], antidepressant [20],…”
Section: Introductionmentioning
confidence: 99%